How Berlusconi will be remembered: notoriety, collective memory and the mediatisation of posterity. Issue 1 (February 2015) - Gundle, Stephen
Abstract : This article explores the ways in which Silvio Berlusconi might figure in collective memory. It approaches this from a number of angles. First, consideration is given to the way political figures of the past have resonated culturally and the role of institutions including the mass media in this. Second, Berlusconi's own efforts to situate himself in relation to a shared past are explored, with reference to the place of three nostalgic appeals that figured with varying intensity at different points in his career. Third, Berlusconian aesthetics are investigated to explore the relative roles of kitsch and glamour. It is shown that kitsch gained the upper hand and that this also manifested itself in the monarchical aspects that his personality cult took on. Finally, Berlusconi is considered as a possible subject for a biopic and a discussion is offered of the way his life and career might be presented in different variants of this genre. Overall, it is suggested that expectations that he will be damned by history fail to take account both of the way he imposed himself on the collective consciousness and of the generic requirements of the mass media.